Relationship between Bruxism and Malocclusion among Preschool Children in Isfahan - Maryam Ghafournia; Maryam Hajenourozali Tehrani (Tabriz University of Medical Sciences, 2012)
Background and aims. Bruxism is defined as a habitual nonfunctional forceful contact between occlusal tooth surfaces. In younger children bruxism may be a consequence of the masticatory neuromuscular system immaturity. The aim of this study was to assess the prevalence of bruxism and investigate the relationship between occlusal factors and bruxism among preschool children. Materials and methods. In this cross-sectional survey, 400 3-6-year-old children were selected randomly from different preschools in Isfahan, Iran. The subjects were divided into two groups of bruxers and non-bruxers as determined by the clinical examination and their parents' reports. The examiner recorded the primary canines (Class I, Class II, and Class III) and molars (mesial step, distal step, flash terminal plane) relationship, existence of anterior and posterior crossbite, open and deep bite. Also, rotated teeth, food impaction, sharp tooth edges, high restorations, extensive tooth caries, and painful teeth (categorized as irritating tooth conditions) were evaluated. The relationship between bruxism and occlusal factors and irritating tooth conditions was evaluated with chi-square test. Results. Bruxism was seen in 12.75% of the subjects. Statistically significant relationships existed between bruxism and some occlusal factors, such as flash terminal plane (P = 0.023) and mesial step (P = 0.001) and also, between food impaction, extensive tooth caries, tooth pain, sharp tooth edge and bruxism. Conclusion. The results showed significant relationship of bruxism with primary molar relationships and irritating tooth conditions among preschool children.